Degradation of Fructans and Production of Propionic Acid by Bacteroides thetaiotaomicron are Enhanced by the Shortage of Amino Acids - Adamberg, Signe; Tomson, Katrin; Vija, Heiki; Puurand, Marju; Kabanova, Natalja; Visnapuu, Triinu; Jõgi, Eerik; Alamäe, Tiina; Adamberg, Kaarel (Frontiers in Nutrition, 2014)
Bacteroides thetaiotaomicron is commonly found in the human colon and stabilizes its ecosystem by catabolism of various polysaccharides. A model of cross-talk between the metabolism of amino acids and fructans in B. thetaiotaomicron was proposed. The growth of B. thetaiotaomicron DSM 2079 in two defined media containing mineral salts and vitamins, and supplemented with either 20 or 2 amino acids, was studied in an isothermal microcalorimeter. The polyfructans inulin (from chicory) and levan (synthesized using levansucrase from Pseudomonas syringae), two fructooligosaccharide preparations with different composition, sucrose and fructose were tested as substrates. The calorimetric power-time curves were substrate specific and typically multiauxic. A surplus of amino acids reduced the consumption of longer oligosaccharides (degree of polymerization > 3). Bacterial growth was not detected either in the carbohydrate free medium containing amino acids or in the medium with inulin as a sole carbohydrate. In amino acid-restricted medium, fermentation leading to acetic acid formation was dominant at the beginning of growth (up to 24 h), followed by increased lactic acid production, and mainly propionic and succinic acids were produced at the end of fermentation. In the medium supplemented with 20 amino acids, the highest production of d-lactate (82 ± 33 mmol/gDW) occurred in parallel with extensive consumption (up to 17 mmol/gDW) of amino acids, especially Ser, Thr, and Asp. The production of Ala and Glu was observed at growth on all substrates, and the production was enhanced under amino acid deficiency. The study revealed the influence of amino acids on fructan metabolism in B. thetaiotaomicron and showed that defined growth media are invaluable in elucidating quantitative metabolic profiles of the bacteria. Levan was shown to act as an easily degradable substrate for B. thetaiotaomicron. The effect of levan on balancing or modifying colon microbiota will be studied in further experiments.